2019
DOI: 10.18203/2349-3933.ijam20195166
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological study of post-operative wound infections with special reference to MRSA and ESBL in a tertiary care hospital

Abstract: Background: Surgical site infections are known to be one of the most common causes of nosocomial infections worldwide and raises an important public health concern.Methods: A prospective observational study was conducted across 12 months (July 2018-June 2019) in a tertiary care hospital. The present study includes 50 pus samples from clinically suspected cases of post-operative wound infections from various surgical wards which were inoculated in Department of Microbiology. The phenotypic identification of dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…On the other hand a study by Rajput et al, (2019) reported 22.72% ESBL producing Escherichia coli, 15.9% ESBL producing Klebsiella pneumonia. A study by Zahran et al,reported 88.2% MRSA,62.5% MRCONS, 65.1% ESBL producing Enterobacteriace and 73% carbapenem resistant which is not similar to the present study.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand a study by Rajput et al, (2019) reported 22.72% ESBL producing Escherichia coli, 15.9% ESBL producing Klebsiella pneumonia. A study by Zahran et al,reported 88.2% MRSA,62.5% MRCONS, 65.1% ESBL producing Enterobacteriace and 73% carbapenem resistant which is not similar to the present study.…”
Section: Resultsmentioning
confidence: 94%
“…coli and 15.9% of Klebsiella were extended-spectrum beta-lactamases producing strains. 13 Similarly, Patel et al also documented increasing emergence of MRSA in 54.8% surgical infections in India. 14…”
Section: Challenges To Healthcare Workersmentioning
confidence: 91%
“…Using the second swab, pus samples were inoculated on Blood agar, MacConkey agar and Thioglycolate broth and were incubated aerobically at 37°C for 18-24 hours. In case of no growth on plates after 24 hours, the respective Thioglycolate broth were examined for turbidity and subcultured if required 11,12 . The bacterial colonies obtained were further processed and identified conventionally, based on colony morphology on culture plates and standard biochemical tests.…”
Section: Microscopy Culture and Sensitivity Testingmentioning
confidence: 99%